The concern of University of Malaya Library in enhancing the facilities for the special disables users - Mohd Faizal, H.; Amir Hamzah, A.; Mohamad Rizar, M. (2013)
Special Disable Users (SDU) is one of the categories of users that use library in University of Malaya Library (UML). According to Act 658, persons with disabilities shall have the right to access to information, communication and technology on equal basis with persons without disabilities (Persons with Disabilities Act 2008, Act 685).The purpose of this article is to point out all the initiatives led by University of Malaya Library (UML) to improve the library services for the visually impaired and physically handicapped students and staffs registered as library members. This initiative was taken to support the mission and vision of the university to produce quality research and knowledgeable students. Special facilities and services should be developed to help these categories of users to use the library. A survey conducted by UML to identify the efficiency of each service provided to engage the library services with that specific group. The result of the survey will be a guideline for UML to improvise the library services to that particular user group. As a conclusion, it is important to make sure UML can provide special library services concerning the specific user group, thus ensuring “a library for everyone”.